(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
The relations between Regency of Algiers and Spain during the Ottoman era were characterized by hostility and wars. Were there economic and commercial relations between them, especially those that linked the two countries? in this study, we will show the face of trade relations between the two countries. Commercial relations between them go back to the year 1786, when the first peace treaty was concluded between them. the 1792 treaty concluded between them increased the pace of commercial activities. many spanish commercial companies have established centers in Regency. The Algerian company Bakri and Boujennah took over its commercial activity with some Spanish coastal cities and Alicante. In this research, we will learn about the most important goods exchanged between the two countries between the years 1786 and 1830, and the most important coastal cities that exported and received goods. Keywords : Regency of Algiers, Spain, trade, port, company, wheat